2006
DOI: 10.2298/soc0604289p
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of traditionalist value orientations in Serbia

Abstract: Systematic failures in attempts to modernize Serbian society during the past two centuries have led to the survival of traditionalist value orientations. The long period of Ottoman rule allowed patriarchal, warrior-tribal cultural patterns to persist and shape the basis for national and overall cultural identity. Extreme poverty, autarkical agricultural production, the slow penetration of capitalism and a market economy, an undifferentiated social structure with majority of rural population, patriarchal organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
1
3
0
3
Order By: Relevance
“…Th e studies so far have indicated a high level of value inconsistency among the Serbian population (Lazić, 2011;Pešić, 2006;Pešić, 2017). Th at insight warns that it is not possible to expect surgically separated ideological positions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Th e studies so far have indicated a high level of value inconsistency among the Serbian population (Lazić, 2011;Pešić, 2006;Pešić, 2017). Th at insight warns that it is not possible to expect surgically separated ideological positions.…”
Section: Resultsmentioning
confidence: 99%
“…Досадашња истраживања су указала на висок ниво вредносне неконзистентности у популацији Србије (Lazić, 2011;Pešić, 2006;Pešić, 2017). Тај увид упозорава да није могуће очекивати хируршки раздвојене идеолошке позиције.…”
Section: резултатиunclassified
“…In shaping the cultures of parenthood in Serbia, the familistic pattern is significant: a high value is placed on the family and its formation as a life goal, which makes it central to the transition to adulthood (Tomanović and Ignjatović, 2010). Other characteristics include a hetero-normative frame of married couples with children and a high level of measured support to patriarchal values and attitudes, especially in relation to gender roles in the private sphere (Pešić, 2006). A significant feature of the dominant ideology of familism in Serbia is the ethics of parental sacrifice for the benefit of their children and their best interests, which is supported by a majority of parents .…”
Section: Gender Regime and Cultures Of Parenthoodmentioning
confidence: 99%
“…На основу поређења података из 1989. и 2004. године, Јелена Пешић закључује да традиционалне вредности у Србији остају доминантне, и подразумевају оријентисаност ка колективизму, висок скор на скали ауторитарности и висок степен патријархалности -традиционално схваћена подела послова између полова, дистинкција јавно-приватно и начин одлучивања у породици (Pesic, 2006).…”
Section: поларизација породичних вредностиunclassified
“…на паралелно постојање предмодерности, модерности и постмодерности. Постоје рационалне вредности али су присутне и вредности преживљавања (Pesic, 2006). Посебно је истицано да поменута трансформација није заобишла ни сферу породице и брака, тј.…”
unclassified